Kangaroo morphometrics: how Miocene kangaroos can inform us about palaeoenvironments and how giant Pleistocene kangaroos managed to locomote - Janis, Christine Marie (My University, 2015)
Kangaroos are known today for their spectacular hopping locomotion, but kangaroo diversity in the past tells a different story. Some kinds of extinct kangaroos (sthenurines) grew so large that hopping would seem to be unlikely. Analysis of their bones shows that it is likely that they used walking on two legs as a means of getting around. The diversity of small kangaroos in the Miocene can inform us about palaeoenvironments, and how the higher levels of both temperature and atmospheric carbon dioxide in the middle Miocene affected the evolution of both fauna and flora.
Keywords: Canguros; Morphometrics; Ecomorphology; Kangaroo